2012
DOI: 10.1016/j.joca.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Rasch analysis of the intermittent and constant osteoarthritis pain (ICOAP) scale

Abstract: SummaryObjectivesThe Intermittent and Constant Osteoarthritis Pain (ICOAP) questionnaire was developed to assess two forms of pain reported by people with osteoarthritis: intermittent and constant pain. Studies examining its measurement qualities have provided some support for its use as separate and total scales. However, it has not been previously evaluated using Rasch analysis. The current study examined the fit between data obtained from the ICOAP questionnaire and the Rasch model to determine whether it m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 26 publications
(31 reference statements)
2
37
1
Order By: Relevance
“…Rasch‐converted scores were used in correlation analyses for both the questionnaire study and the PPT substudy, when available (for review, see ref. 14). Use of ICOAP subscale scores was supported by previous analyses 14.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rasch‐converted scores were used in correlation analyses for both the questionnaire study and the PPT substudy, when available (for review, see ref. 14). Use of ICOAP subscale scores was supported by previous analyses 14.…”
Section: Methodsmentioning
confidence: 99%
“…14). Use of ICOAP subscale scores was supported by previous analyses 14. When appropriate, 95% confidence intervals (95% CIs) were calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated by the Rasch analysis of the ICOAP [21], items 2, 8 and 11 were removed and as these items related to sleep and well-being; a separate ICOAP subscale was then created with these items. Rasch-analysis of the CPAQ [25] indicated that that the two CPAQ subscales, Activity Engagement (AE) and Pain Willingness (PW), should be analysed as separate scales.…”
Section: Methodsmentioning
confidence: 99%
“…Rasch analysis is a psychometric technique, which can be applied to both newly developed and existing questionnaires, enabling the advanced analysis of different measurement issues [21][22]. Data on an outcome measure are tested against the predictions of the Rasch model [24].…”
Section: Introductionmentioning
confidence: 99%